Pemanfaatan Fitur Z39.50 pada SLiMS (Studi Kasus di Perpustakaan Fakultas Adab dan Humaniora UIN Alauddin) - Syukur, Abdul; Mathar, Taufiq; Azwar, Muhammad (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
Z39.50 is an international standard client–server, application layer communications protocol for searching and retrieving information from a database over a TCP/IP computer network. The current study is focused on how the Z39.50 fiture at SLiMS being used by the FAH library staff. The purposes of the study are divided into two which are (1) to know library staf’s perception on the fiture, and (2) to know the difficulties faced by the staf to do copy cataloging from the Library of Congress server. The data was gathered through the library staf experiences and being qualitatively analysed. The study found that the library has been using Z39.50 protocol to copy cataloging English book collections from the Library of Congress server since 2015. Although it makes easier the library to catalog, but some fields need to be edited by the library staf